Cost-effectiveness of tenofovir in the treatment of patients with chronic hepatitis B: data from literature - Fasano, Massimo; Colombo, Giorgio L.; Di Matteo, Sergio; Randazzo, Claudia; Angarano, Gioacchino; Santantonio, Teresa Antonia (Farmeconomia. Health Economics and Therapeutic Pathways, 2014)
Chronic hepatitis B (CHB) is a complex disease with significant social impact both on the patients’ quality of life of and the economic resources involved. Its chronicity affects considerably not only the clinical management of the disease (for the need for drugs with proven long-term safety and low rate of resistance), but also the economic impact (for the high costs of treatment, the management of complications, and the constant monitoring of therapy).Since, as is well known, the main problem of modern health care systems is the general scarcity of available resources in the face of growing demand for health, the issue of economic evaluation of therapies for the treatment of chronic hepatitis B has been addressed in numerous national and international studies. In fact, clinicians find a strong support for the choice of the most suitable therapeutic pathway in the major scientific societies’ guidelines (European Association for the Study of The Liver – EASL, American Association for the Study of Liver Diseases – AASLD, Associazione Italiana per lo Studio del Fegato – AISF), while the analysis of the economic implications is rather more difficult, even for the methodological differences and peculiarities of the different countries.The aim of this paper is to present a brief summary of some of the recently conducted cost-effectiveness analyses and extrapolate some data to support the economic evidence related to the treatment of CHB with nucleos(t)ide analogs. In particular, the article focuses on the comparison between entecavir (ETV) and tenofovir (TDF), the two oral antiviral therapies recommended for first-line treatment. In the selected studies, the comparison between the different treatment options was conducted in order to assess the incremental cost-effectiveness ratio (ICER) and the results were expressed in terms of QALYs (Quality Adjusted Life Years) gained.Despite the methodological differences among the selected studies, tenofovir is found to be, in the context of first-line oral antiviral therapies, the most cost-effective treatment for patients with chronic hepatitis B.